Development and Implementation of Indoor Location-based Service in Museums Based on Bluetooth Low Energy Standard and Triangulation Algorithm - Aras Khosravi; Younes Seddighi; Parviz Zeaiean Firouzabadi (International Journal of Wireless Security and Networks, 2024)
Location-based services (LBS) in indoor locations are for providing information needed by users, and this information can be provided to users based on a Geofence. The most important component of location-based service systems is the Global Positioning System (GPS), which does not have the ability to determine the location in an indoor location. In this research, LBS Android software was developed for museums with the possibility of providing multimedia information based on the Geofence concept. The visitor is first positioned by Indoor Positioning System (IPS) in this software, and multimedia information is presented to the visitor by being placed in the Geofence. To determine the user’s location, Bluetooth Low Energy (BLE)-based transmitters were installed, and the Trilateration algorithm was used to develop a two-dimensional positioning system in an indoor location. The main input variables of this algorithm were the distance of the transmitters from the user and the X and Y coordinates related to the installation location of the transmitters. Received Signal Strength Indicator (RSSI) was used to obtain the distance between the visitor and the transmitters, and the coordinates of the transmitters were measured in terms of X and Y dimensions relative to the reference point. The positioning accuracy of the system was evaluated based on Root Mean Square (RMS) and apparent errors in the environment. The final apparent error is equal to 1.02975 and the apparent error range is (0.43–1.44) meters.
Keywords: Bluetooth transmitters; Location-based services; indoor positioning; museums; triangulation